PENGARUH PERINGKAT SUKUK, UMUR SUKUK, DEBT TO EQUITY RATIO, DAN TINGKAT SUKU BUNGA TERHADAP IMBAL HASIL SUKUK KORPORASI DI INDONESIA - Masrurah, Fitria; Rahamwaty, Rahamwaty (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This research aimed to test the influence of Sukuk Ratings, Sukuk Maturity, Debt to Equity Ratio (DER), and Interest Rate of the corporate Sukuk Yields in Indonesia. The type of research used in this study is quantitative by using secondary data. Data collection was done by searching online data obtained through the website. The variable measurements of Sukuk Yields, Sukuk Maturity, DER, and Interest Rate using ratio scale while Sukuk Ratings using ordinal scale. The sampling technique was determined by purposive sampling. The number of samples used in this research are 33 samples from 11 outstanding sukuk and rated by PT Pefindo during 2014-2016 periods. Data were analyzed by using a multiple linear regression analysis and were processed by IBM Statistical Package for Social Science (SPSS) 21th version. The results of this study indicated that 39.0% of the dependent variable can be explained by four independent variables. This showed that simultaneously variables which were Sukuk Ratings, Sukuk Maturity, DER, and Interest Rate were influence on corporate Sukuk Yields in Indonesia on 2014-2016 periods. For partial influence, it indicated that Sukuk Ratings and Sukuk Maturity effected on corporate Sukuk Yields in Indonesia 2014-2016 periods. By contrast, DER and Interest Rate had no effect on corporate Sukuk Yields in Indonesia 2014-2016 periods.